Development of the PAI Curriculum System through Integration of Riwāyah Aḥmad No. 8952: Pengembangan Sistem Kurikulum PAI melalui Integrasi Riwāyah Aḥmad No. 8952 - Bildan Muhammad Sya'ban; Elan Sumarna; Cucu Surahman; Muhammad Hizba Aulia (Jurnal Living Hadis, 2025)
In recent years, various moral issues such as bullying, individualism, and diminished social awareness among students have emerged as critical concerns in education. In response to this, it becomes imperative to examine the concept of akhlāq (moral character) within Islamic education, particularly through the integration of the Prophet’s hadith into the Islamic Religious Education (PAI) curriculum. This research posits two central questions: first, what is the meaning of riwāyah Aḥmad No. 8952, and second, how can the values encapsulated in this hadith be effectively implemented to optimize the function of the PAI curriculum? These questions are analyzed using a qualitative-descriptive methodology, employing a literature study approach that involves a comprehensive review, examination, and comparison of various hadiths and Islamic educational texts. The findings suggest that the conceptual emphasis on akhlāq, which underscores its central role as the primary mission of prophethood, should serve as the foundational framework for the PAI curriculum. Furthermore, the research identifies the application of a Deep Learning approach incorporating Mindful, Meaningful, and Joyful Learning strategies as a promising method for internalizing akhlāq values into students’ lives.